The effect of immunosuppression on outcomes in elderly patients with community-acquired pneumonia - Lixue Huang; Bingxuan Weng; Yuanqi Wang; Mengyuan Wang; Yin Mei; Wei Chen; Meng Ma; Jingnan Li; Jianzhen Weng; Yang Ju; Xuefeng Zhong; Xunliang Tong; et al. (Respiratory Research)
Abstract Background The effect of immunosuppression on clinical manifestations and outcomes was unclear in elderly patients with CAP. Methods Elderly hospitalised patients with CAP were consecutively enrolled and were divided into immunocompromised hosts (ICHs) or non-ICHs groups. Clinical manifestations, severity, and outcomes were compared. The logistic regression model was used to determine the association between immunosuppression and outcomes. The primary outcome was 30-day mortality. Results A total of 822 patients were enrolled, of whom 133 (16.2%) were immunocompromised. There were no differences between the two groups in vital signs, oxygenation, admission laboratory tests, need for mechanical ventilation and intensive care unit admission, except for a lower lymphocyte count in the ICH group (0.9*10^9/L, IQR 0.6–1.3*10^9/L [ICH group] vs. 1.2*10^9/L, IQR 0.8–1.7*10^9/L [non-ICH group]; p < 0.001). The 30-day mortality in ICHs was 15.8%, significantly higher than the 5.1% in non-ICHs (p < 0.001). The risk distribution of severity was similar between the two groups when assessed by CURB-65 on admission; however, the significant difference was found when assessed by PSI. Notably, in the CURB-65 low-risk group, the 30-day mortality was significantly higher in ICHs than in non-ICHs (9.7% vs. 1.1%, p < 0.001); but there was no difference between ICHs and non-ICHs in PSI low-risk group (3.7% vs. 0.6%; p > 0.05). After adjusting for age, sex, and comorbidities, immunosuppression was significantly associated with a higher risk of 30-day mortality (odds ratio 5.004, 95% CI [2.618–9.530]). Conclusions Immunosuppression was independently associated with an increased risk of 30-day mortality. CURB-65 may underestimate the mortality risk of ICHs.